Poética alto xinguana: a metáfora do abrigo - uma etnografia da casa - Malhano, Hamilton Botelho (1993)
This learning intendes to discover upper xinguan residential house in this region indians groups aesthetic thought, of Tupi, aruak and Karibe languages were-spoken, We started our research through a metaphor, the shelter metaphor: house, while "cultural" entity, shelts human body, "natural" entity; human body; while "natural" entity, shelts the knowledge, the most inclusive "cultural" entity.